Քաշաթաղի 17-րդ դարի պատմությանը վերաբերող մի փաստաթուղթ - Կոստիկյան, Քրիստինե («Զանգակ - 97»)
The Persian document examined in the article is a kind of conunon application addressed to the court ef Shah Soltan Huseyn, confirmed by a number of Armenian and Moslem high officials and noblemen. It is'written on behalf of Melik Hakhnazar of Kashatagh, most likely from the noble family of Melik-Haykazyans and the Aimenian village-elders of that region. The document is firm evidence, that this region of Siwnik, which corresponds to nowadays Kashatagh (Lachin) region of the Republic of Karabagh, had Armenian population on the whole at the end 17th Century, makdng joint efforts to protect its rights before Persian administration.
Keywords: Հայոց պատմություն